IMPLEMENTASI KEBIJAKAN BARANG MILIK DAERAH (Studi Kasus Sengketa Lahan di Jaian Ngamglik 27-29 Surabaya - Rezky Herdhitya Pratama; Mas Roro Lilik Ekowanti (Aplikasi Administrasi: Media Analisa Masalah Administrasi, 2014)
The purpose of this study are: (I) Determine the implementation Surabaya Regional Regulation No. 14 of 2012 on sectorial asset management area. (2). Analyzing the implementation of the application constraints Surabaya Regional Regulation No. 14 of 2012 on asset management area is located at 27-29 Ngaglik Surabaya. This study was a descriptive study Descriptive study (descriptive research). The residts of conceptual standards and objectives Regulation No. 14 The year 2012 is not clear, communication with outlying agencies DJKNyet, disposition is not consistently continue to province, so that the land conflict is still going on in the legislature. Surabaya City Regional Regulation No. 14 of 2012, particularly implemented in asset building in Ngaglik street No. 27-29 Surabaya very difficult to implement because these assets are assets of foreign heritage / china. Conclusion: Bylaw has not run as expected, while the inhibiting factor: the lack of standards and policy goals, communication with citizens is not the way, and a disposition less consistent. Suggestion: SKPD related to the implementation of the Asset Management conduct: (I), mediation with citizens. (2). optimize MoUwith DJKNXand BPN Surabaya region to help resolve the conflict. (3). Formidation laws with entering a foreign land